THE EFFECT OF OPENING DISTRIBUTION AREA MODIFICATION ON HORIZONTAL LIGHT PIPE DAYLIGHT PERFORMANCE - Feny Elsiana; Sri Nastiti Ekasiwi; I Gusti Ngurah Antaryama (DIMENSI (Journal of Architecture and Built Environment), 2020)
A deep-plan office building design limits daylight access on the workspace distant from the side window. Horizontal Light Pipe (HLP) is one of the light transport systems that can deliver daylight to these areas. The research aim was to explain and evaluate the effect of HLP’s opening distribution area on daylight performance at deep plan-private office space. The research method was experimental with simulation as a tool. Daylight level and distribution of the base case, HLP with an opening distribution area of 6.6 m2 were compared with the case, HLP with an opening distribution area of 3.41 m2. The results showed that both cases distributed daylight uniformly. A 50% reduction of HLP’s opening distribution area, from 6.6 m2 to 3.41 m2 improved the average Daylight Factor as big as 6.42%. HLP with a smaller opening distribution area can be applied as the main source of daylight on deep-plan office spaces